2019
DOI: 10.3390/jcm8101585
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Longitudinal Changes in Blood Pressure

Abstract: Hypertension is the leading risk factor for premature death worldwide. The identification of modifiable causes of hypertension remains an imperative task. We aimed to investigate associations between 79 proteins implicated in cardiovascular disease and longitudinal blood pressure (BP) changes in three Swedish prospective cohorts. In a discovery phase, we investigated associations between baseline circulating protein levels assessed with a proximity extension assay and BP stage progression at follow-up 5 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…We only found 3 cross-sectional studies with small sample sizes 6 8 and 1 longitudinal study. 10 A few previously reported proteins in the 3 cross-sectional studies were replicated in our discovery analysis, including latency-associated peptide TGF-β1 (transforming growth factor beta-1), 7 TNFRSF14 (tumor necrosis factor receptor superfamily member 14), and PLC (perlecan). 8 Using the same protein measurement technology as in the present study, Lin et al 10 identified REN from 79 plasma CVD I–based proteins, showing a positive association with BP progression in the discovery cohort only.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…We only found 3 cross-sectional studies with small sample sizes 6 8 and 1 longitudinal study. 10 A few previously reported proteins in the 3 cross-sectional studies were replicated in our discovery analysis, including latency-associated peptide TGF-β1 (transforming growth factor beta-1), 7 TNFRSF14 (tumor necrosis factor receptor superfamily member 14), and PLC (perlecan). 8 Using the same protein measurement technology as in the present study, Lin et al 10 identified REN from 79 plasma CVD I–based proteins, showing a positive association with BP progression in the discovery cohort only.…”
Section: Discussionsupporting
confidence: 54%
“…To date, there is only 1 longitudinal proteomic study on primary hypertension. Lin et al 10 investigated the associations of 79 plasma CVD-related proteins with BP progression over 5 years and found that REN was positively associated with BP progression in the discovery cohort (n=804) but not in the validation cohort (n=2659). Only 2 repeated measurements of BP were included in their longitudinal analysis, with a relatively short follow-up duration.…”
mentioning
confidence: 99%
“…Modules or clusters of proteins were identified by weighted correlation network analysis (WGCNA) using a Pearson-based weighted adjacency matrix (signed, β=14) and average linkage hierarchical clustering 23 . Modules were evaluated for enriched biological processes 24 and used to compare study associations with the differential protein profiles of other diseases including myocardial infarction (MI) [25][26][27] , cardiovascular-related death (CVD) / heart failure (HF) 27 , stroke 27,28 , hypertension 29 , atherosclerosis 30 , diabetes 31 , smoking 32 , kidney function 33 , and chronic kidney disease (CKD) 33 . Findings were not significantly affected after correcting for sample handling, although there was a minor improvement in the variability ( Supplementary Table S2, S3).…”
Section: Differences In Protein Levels Between Covid-19 Positive Patimentioning
confidence: 99%
“…19 After discharge, the treatments were consistent with 2013 AHA/ASA guidelines for the prevention of stroke in patients with stroke and transient ischemic attack. 19 Supine BP was measured by trained nurses with a standard mercury sphygmomanometer 20 , 21 , 22 , 23 , 24 (YUTU‐XJ11E; Medical Instrument Co, Shanghai, China) on the non‐paralyzed arm every 4 h for 3 days after stroke onset. Blood pressure was measured two consecutive readings between each measurement.…”
Section: Methodsmentioning
confidence: 99%
“…19 After discharge, the treatments were consistent with 2013 AHA/ASA guidelines for the prevention of stroke in patients with stroke and transient ischemic attack. 19 Supine BP was measured by trained nurses with a standard mercury sphygmomanometer [20][21][22][23][24]…”
Section: Blood Pressure Measurementmentioning
confidence: 99%